Microanalysis of Root Cementum in Patients with Aggressive Periodontitis - Soliman O. Amro; Hisham I. Othman; Mohammed S. Al Zahrani (Journal of King Abdulaziz University: Medical Sciences, 2023)
The purpose of this study was to evaluate the microanalysis of various elements, and assess the surface characteristics of aggressive periodontally diseased roots in comparison to sound root surface. Fifty teeth were collected: 25 from patients with aggressive periodontitis, and 25 teeth from healthy patients. Measurements of probing depth and clinical attachment loss were taken prior to extractions. Healthy and diseased root cementum were evaluated by scanning electron microscopy and energy dispersive X-ray spectroscopy. The collected data were statistically evaluated using t-test. The level of significance was set at p < 0.001. The results of this study showed a significant decrease in the calcium and phosphate contents along the entire root cementum of the aggressive periodontitis and a significant increase in the magnesium and sulphur of the same root in comparison to the control group. In addition, there were remarkable destructions of cementum, crack lines and deep cavities reaching to the underlying dentin. In conclusion, the alteration in cementum structures and composition due to aggressive periodontitis might have an important implication on periodontal therapy. The influence of alteration of cementum.